PENINGKATAN PRODUKTIVITAS USAHA KERAJINAN TEMPURUNG KELAPA MELALUI KONSEP PROSES PRODUKSI TERPADU - Paryanto, Paryanto; Rahmawaty, Penny; Ardian, Aan (Universitas Negeri Yogyakarta, 2013)
The event was held with the aim to improve the productivity of coconut shell craftsmen (bathok) in the village of Santan and Ngimbang Bantul, using the concept ofIntegrated Production Process. These objectives are translated into specific objectives, namely procurement of appropriate technology, improve the ability of craftsmen in business management, and improve the ability of craftsmen in the use of the internet as a marketing medium. The concept of integrated production processes are translated into three activities: procurement of appropriate technology, the Internet as a marketing medium for training, and business management training.This activity is carried out by using lectures, discussions, demonstrations, handson and observation. Lecture method is used in the process of delivering training materials. Besides, it is also used in providing motivation to craftsmen to always defend and promote the spirit of trying as a major capital in increasing productivity of the craftsmen. Discussion method is used as a medium ofcommunication with the training to take place resulting in a two-way communication between the presenters and artisans. The method used in the demonstration of an example in every training, thus providing facilities to the artisans in understanding the material presented. The method used to apply a hands-on materials that have been obtained, of course, with the guidance of presenters. Observation methods performed to observe the craftsmen skills both during the training and after the training. Observations after the training aimed to determine the impact of the training that has been conducted related to the progress of the productivity of the craftsmen. The results of this activity are: (1) has been assigned some appropriate technology equipment that is 2 units of portable drilling machine, 1 unit sanding machine and 1 unit compressor, (2) business management training can improve the ability of craftsmen in the fields of management, which is 70% craftsmen have acquired in the management of the business, (3) training using the Internet can enhance the ability of artisans to utilize the internet as a marketing medium, which is 40% craftsmen have the ability to use the Internet, (4) based on the results of the analysis of increased productivity, increased artisans revenues of approximately 30%Keywords: concept of integrated production processes, coconut shellcraftsmen